Model and Properties of Exponentiated Generalized Odd Lomax Exponential Distribution - Telee, Lal Babu Sah; Karki, Murari; Kumar, Vijay (Interdisciplinary Journal of Management and Social Sciences, 2023)
This study is based on the formulation of new probability model called Exponentiated Generalized Odd Lomax Exponential Distribution using Odd Lomax Generator and the exponential distribution. Some statistical properties like survival function, hazard rate function, quantile function and random deviate generation of the model is studied. Parameters of the model are estimated using Maximum likelihood, least square and Cramer – von Mises method methods of estimation. Applicability of the model is studied taking a real COVID - 19 data set. For model comparison, different information criteria like Akanke, Bayesian, and corrected Akaike criteria are used and the goodness of fit of the proposed model is test using Kolmogrov - Smirnov, Cramer – von Mises and Anderson Darling method. To compare the suitability of the model, some already defined probability models are considered and compared on basis of different criteria. To study of the performance of MLEs, Monte - Carlo simulation is presented. All the calculations are performed using R programming language.